2018
DOI: 10.1016/j.theriogenology.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Simple storage (CO2-free) of porcine morulae for up to three days maintains the in vitro viability and developmental competence

Abstract: The advancement of porcine embryo transfer (ET) technology is constrained by regulatory hurdles (liquid nitrogen transportation) or, more importantly, the technical obstacles of using vitrified embryos in combination with nonsurgical deep uterine ET technology. Maintaining embryos in culture during transport and prior ET collides with the need of CO gassing and the best choice of culture medium. In this work, we describe storage conditions for short-term embryo CO-free storage that allowed for a majority of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 29 publications
(36 reference statements)
5
29
0
1
Order By: Relevance
“…Pomar et al () reported that short storage at 25°C is more suitable for maintaining the quality and development of porcine in vivo‐produced embryos. Moreover, storage medium has been suggested to play an important role for short storage of porcine embryos at hypothermic temperatures (Martinez et al, ; Pomar et al, ). In the current study, we found that when the porcine zygotes were stored at 25°C for 24 hr, more zygotes stored in 100% FBS developed to the blastocyst stage compared with BSA‐containing TCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pomar et al () reported that short storage at 25°C is more suitable for maintaining the quality and development of porcine in vivo‐produced embryos. Moreover, storage medium has been suggested to play an important role for short storage of porcine embryos at hypothermic temperatures (Martinez et al, ; Pomar et al, ). In the current study, we found that when the porcine zygotes were stored at 25°C for 24 hr, more zygotes stored in 100% FBS developed to the blastocyst stage compared with BSA‐containing TCM.…”
Section: Discussionmentioning
confidence: 99%
“…Serum additives or bovine serum albumin (BSA)‐based preparations have been used as supplements for the hypothermic preservation of mammalian embryos (Ideta et al, ; Martinez et al, ). Ideta et al () reported that the addition of serum with a high concentration in the storage medium enhances viability of bovine embryos after hypothermic preservation compared with BSA addition.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, despite the embryonic developmental delay observed at the end of storage, these embryos generated high fertility rates and prolificacy after NsDU‐ET into recipients (Martinez et al., ). Later, we described CO 2 ‐free storage conditions to support the survival of morulae (Martinez et al., ) and blastocysts (unpublished data) for 72 hr and 48 hr, respectively, and to allow their development to the unhatched blastocyst stage. These conditions included NCSU‐23 medium with 0.4% BSA at 37°C (morulae) or 25°C (blastocysts).…”
Section: Research On Embryo Storage In Liquid Statementioning
confidence: 99%
“…In another recent study, we evaluated the potential of prolonging the liquid-storage period for up to 72 h after collection. Morulae stored at 37 °C 6 and blastocysts stored at 25 °C (unpublished data) in a semi-defined medium containing 0.4% BSA maintained their in vitro viability and developmental competence for up to 72 h. However, although these embryos exhibited an important development delay compared to controls, many of them hatched after 72 h of storage. Additional efforts are thus needed to identify alternative storing conditions that would allow for overseas shipment of un-hatched embryos in a liquid state.…”
Section: Introductionmentioning
confidence: 94%